Repetitive head impacts in a collegiate football season: Exposure and effects - Wilson, L. D.; Hildebrand, R. A.; Le, T.; McKinney, B. A. (International Journal of Sports Science & Coaching, 2022)
This study describes exposure to repetitive head impacts (RHI) by player position and activity during a collegiate football season, and investigates the relationship between RHI and acute (i.e., daily and weekly) and short-term (i.e., pre- to post-season) changes in balance, reaction time, symptoms, and cognition. We recorded RHI exposure in twenty Division I collegiate American football players during a single season using the Riddell InSite system. Participants sustained 4,586 impacts (4.20% high impact, i.e., >63 g; 95.79% low impact, i.e., 20 63 g). Greatest exposure to RHI was observed in running backs and defensive ends during games, and tight ends and defensive ends during practices. Running plays and team drills placed players at greatest risk for exposure during practice. Cumulative RHI exposure across the season was associated with short-term declines in reaction time (p = 0.045), but not balance or cognition. Acute decline in balance was associated with the number of impacts sustained in the past week (p < 0.05), but not the past 24 hours (p > 0.05). Acute increase in total symptom score was also associated with the number of impacts sustained in the past week (p < 0.01), but not the past 24 hours (p > 0.05). Reaction time did not decline based on impact exposure in the past 24 hours or week. This study identifies activities and positions that may put players at risk for RHI exposure, and demonstrates that RHI sustained during the course of typical American football play by non-concussed individuals may result in small changes in balance, reaction time, and symptoms, but not cognition.